The use of neoadjuvant chemotherapy in advanced endometrial cancer - L. Philp; A. Kanbergs; J. St. Laurent; W.B. Growdon; C. Feltmate; A. Goodman (Elsevier, 2021)
The objective of this retrospective cohort study was to review the use of neoadjuvant chemotherapy followed by interval cytoreductive surgery in patients presenting with advanced, unresectable endometrial cancer at two large cancer centers. Patients with advanced endometrial cancer treated with neoadjuvant chemotherapy between 2008 and 2015 were identified from an institutional database. Clinical and surgical variables were analyzed and time to recurrence and death was calculated and compared between surgical groups. Thirty-three patients were identified (mean age 64.8 (range 42-86 years)). Overall, 28% of patients had endometrioid histology, 48% serous, 4% clear cell, 4% carcinosarcoma, 12% mixed and 4% other. Ineligibility for primary surgery was due to unresectable disease (85%), comorbidities (6%) and unknown reasons (9%). All patients received neoadjuvant chemotherapy with 91% of patients receiving carboplatin and paclitaxel. On reimaging, 12% of patients had progressed, 76% had a partial response and 3% had a complete response to chemotherapy. 76% of patients underwent interval surgery, with cytoreduction to no visible residual disease achieved in 52%. Overall, 91% of patients recurred and 85% died during follow-up. Patients undergoing surgery after chemotherapy had significantly longer progression-free survival (11.53 vs. 4.99 months, p = 0.0096) and overall survival (24.13 vs. 7.04 months, p = 0.0042) when compared to patients who did not have surgery. Neoadjuvant chemotherapy is a feasible treatment option to allow for interval cytoreductive surgery in patients with advanced endometrial cancer not amenable to primary debulking. Patients who undergo surgery after chemotherapy have significantly improved progression free and overall survival.